Electromagnetic heating using nanomaterials and various potentials applications - Phuc, Nguyen Xuan; Do Hung Manh,; Pham Hong Nam, (Vietnam Journal of Science and Technology, 2023)
Electromagnetic heating (EMH) is a process of adsorbing electromagnetic wave energy by a material and converting it into heat. Nanomaterials can serve as novel susceptors in EMH due to the fine size that made them become heat sources from inside, as well as because of new heating mechanisms such as Neel relaxation by magnetic nanoparticles (MNPs) and localized surface plasmon resonance by metallic nanostructures. This review firstly introduces general theoretical & experimental aspects of the alternating electric field (AEF)- and magnetic field (AMF)-stimulated heating. Next, attempts to fabricate MNPs and photothermal nanoparticles (PNPs) of improved heating efficiencies have been reviewed and those with the highest specific loss power have been summarized. Finally, potential applications, including cancer treatment using AMF@MNP hyperthermia and AEF@PNP hyperthermia, AMF@MNP- and AEF@PNP- triggered drug release, as well as nanocomposite processing were particularly highlighted. Besides, other exotic applications such as toxic solvent desorption from adsorbent materials, thermophoresis in precise membrane melting as well as optical signal processing in heat-assisted magnetic memory technology were also outlined. The various applications were attempted to represent into 2 groups: biomedicine, and materials processing; which are composed of localized/targeted and volumetric heating type.